The Role of Perceived Social Support in the Association Between Stressful Life Events and Suicidal Behavior - Panesar, Balpreet; Rosic, Tea; Rodrigues, Myanca; Sanger, Nitika; Baptist-Mohseni, Natasha; Hillmer, Alannah; Chawar, Caroul; D'Elia, Alessia; Minuzzi, Luciano; Thabane, Lehana; Samaan, Zainab (Frontiers in Psychiatry, 2021)
Background: Suicide is a serious public health concern for which there have been well-established protective and risk factors reported in literature. There is a lack of evidence on the indirect effects of other variables on these factors. Specifically, the association between stressful life events and suicidal behavior may be affected by perceived social support, but its role in this association is largely uninvestigated. Objectives: Thus, this paper aims to explore the role of perceived social support in the association between stressful life events and suicidal behavior. Perceived social support will be explored as a mediator and as a moderator in this association. Methods: Data were obtained from the Determinants of Suicidal Behavior Conventional and Emergent Risk (DISCOVER), a study conducted to identify risk factors of suicidal behavior. The study participants are individuals with suicide attempts admitted to hospital. Participants (n = 343) were recruited from hospital setting. Suicidal behavior was measured using two outcomes (1) the occurrence of a suicide attempt (2) level of suicide intent as measured by the Pierce Suicide Intent Scale. Perceived social support was measured using the Sarason Social Support Questionnaire. Results: Stressful life events were significantly associated with suicide attempts (OR 1.440, 95% CI 1.440, 1.682, p < 0.001) and perceived social support (B −0.785, 95% CI −1.501, −0.068, p = 0.032). There was no significant mediation effect by perceived social support in the association between stressful life events and suicide attempts (Sobel's test statistic 1.64, p = 0.100). Perceived social support did not moderate the relationship between stressful life events and suicide attempts [(OR 1.007, 95% CI 0.987, 1.027, p = 0.514] or the relationship between stressful life events and level of suicidal intent (B −0.043, 95% CI −0.132, 0.046, p = 0.343). Conclusion: Stressful life events are associated with increased risk of suicide attempts. The study also identified an inverse relationship between stressful life events and perceived social support. These associations were independent of perceived social support. This study highlights the effects of stressful life events on suicide risk is not affected by perceived social support, requiring further investigation into measures to reduce the impact of social stressors on people with risk of suicide.